LAW ENFORCEMENT IN CRIMINAL OFFENCES IN THE 2020 REGIONAL HEAD ELECTIONS (PILKADA) IN BINJAI CITY BY INTEGRATED LAW ENFORCEMENT CENTER (Study on the General Election Supervisory Body of Binjai City) - Khairunnisa; Mirza Nasution; Abdul Aziz Alsa (RADJA PUBLIKA, 2025)
The Unitary State of the Republic of Indonesia is a constitutional state that places the highest sovereignty in the hands of the people, as referred to in Article 1 paragraph (2) of the 1945 Constitution of the Republic of Indonesia, which reads: